2021
DOI: 10.1186/s12864-021-07880-z
|View full text |Cite
|
Sign up to set email alerts
|

circ_0038718 promotes colon cancer cell malignant progression via the miR-195-5p/Axin2 signaling axis and also effect Wnt/β-catenin signal pathway

Abstract: Objective Colon cancer (CC) is one of the most common cancers whose progression is regulated by a number of factors, including circular RNAs (circRNAs). Nonetheless, circ_0038718 is a novel circRNA, and its regulatory mechanism in CC remains unclear. Methods Real-time quantitative PCR (qRT-PCR) was performed to detect the expression of circ_0038718, miR-195-5p and Axin2. Western blot was conducted to determine the protein expression of Axin2 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Reaction (RT-qPCR) Detection. RT-qPCR was performed to detect miRNA and mRNA as mentioned above [20]. Te extraction of total RNA was from NPC tissues and cells adopting TRIzol kit (Invitrogen).…”
Section: Reverse Transcription-quantitative Polymerase Chainmentioning
confidence: 99%
“…Reaction (RT-qPCR) Detection. RT-qPCR was performed to detect miRNA and mRNA as mentioned above [20]. Te extraction of total RNA was from NPC tissues and cells adopting TRIzol kit (Invitrogen).…”
Section: Reverse Transcription-quantitative Polymerase Chainmentioning
confidence: 99%
“…In this study, miR‐195‐5p was identified as the downstream miRNA of CERS6‐AS1 in PC. Previously, it was reported that miR‐195‐5p acts as an antioncogene in many types of cancer, including colon, 24 bladder, 25 lung, 26 and esophageal cancer 27 . For example, lncRNA BANCR was reported to promote the tumorigenesis of PC by targeting miR‐195‐5p and regulating the Wnt/β‐catenin signaling pathway 28 .…”
Section: Discussionmentioning
confidence: 99%
“…CircPVT1 has been proved to locate mainly in cytoplasm, which meant that it might act as microRNA sponges to regulate downstream gene expression. MiR-195 is dysregulated in several tumors, such as colon cancer [ 56 ], non-small lung cancer [ 57 ], laryngeal cancer [ 58 , 59 ], gastric cancer [ 60 ], cervical cancer [ 61 ], colorectal cancer [ 62 ], breast cancer [ 63 ], lung adenocarcinoma [ 64 ] and osteosarcoma [ 65 ]. Moreover, miR-195 has been demonstrated that play a significant role in PTC [ 66–69 ].…”
Section: Discussionmentioning
confidence: 99%